A note on acquisition of complements in a vertically differentiated market - Ornella Tarola; Cecilia Vergari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
This note is concerned with the effects of joint ownership of complements when they are vertically differentiated. We provide strong arguments for the positive nature of network integration among firms, while showing at the same time that, in some circumstances, anti-competitive consequences can be observed under acquisition.
Keywords: L1; L4; 330